Food consumption - Ulijaszek, S; Strickland, S (Smith-Gordon and Company Ltd, 1993)
Patterns of food consumption are of considerable interest to both nutritionists and anthropologists. Nutritionists may perceive that either qualitative or quantitative dietary inadequacies may lead to nutritional problems in the individual, household or community. Ecologically orientated anthropologists seek to explain patterns of consumption using adaptive models which may employ both biological and cultural factors. Of common concern to both is the way in which food is distributed within a population, community or household. Further, both seek to understand the nature and biological effects of food choice and food taboos. In this chapter, various aspects of food consumption patterns will be examined. These include within-household food distribution, the idea of food choice considered from an evolutionary perspective, and the biological effects of food restrictions and taboos.